Systematic Review of Sexual Dimorphism in the Genus Draco (Lacertilia: Agamidae) - Faiq Khoerul Umam (Universitas Batanghari Jambi, 2026)
This systematic literature review synthesizes morphological, ecological, and evolutionary information to understand variation in sexual dimorphism in Draco. The literature indicates that males generally possess conspicuous marking structures such as brightly colored neck skin folds and more differentiated patagia that function in territorial defense and mate attraction. In contrast, females often exhibit proportionally larger body size and patagia area, reflecting natural selection pressures related to reproductive costs and the need to maintain gliding performance while carrying eggs. Patterns of sexual dimorphism in Draco vary widely across species and regions, influenced by local environmental conditions, habitat noise levels, and interspecific competition.